Stimulation of phagocytic activity in the reticuloendothelial systems of mice by lipid A complexed with homologous or heterologous proteins. - Nakano, M (1975)
Heterologous proteins are more suitable carriers than homologous proteins for the expression of endotoxic activity of lipid A prepared from the lipopolysaccharides of Salmonella typhimurium SL1102 (Re form) to stimulate the reticuloendothelial system of mice.